2013
DOI: 10.1074/jbc.m113.471318
|View full text |Cite
|
Sign up to set email alerts
|

Binding of the Sialic Acid-binding Lectin, Siglec-9, to the Membrane Mucin, MUC1, Induces Recruitment of β-Catenin and Subsequent Cell Growth

Abstract: Background: MUC1 plays a role in mediation of signaling initiated by growth factors. Results: Siglec-9-positive cells are associated with MUC1-positive tumor cells in tumor tissues, and Siglec-9 binds to MUC1. Conclusion: MUC1-mediated signaling occurs by direct binding of Siglec-9 to MUC1. Significance: Multiple signaling pathway through MUC1 can be advantageous to adjust to various conditions of tumor microenvironments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
55
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 37 publications
1
55
2
Order By: Relevance
“…6). In addition, we previously reported that EGFR was not co-immunoprecipitated with MUC1 in HCT116/MUC1 cells (33). Thus, these findings suggest that phosphorylation of MUC1-CD by galectin-3 and subsequent phosphorylation of ERK1/2 and Akt occur independently of EGFR.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…6). In addition, we previously reported that EGFR was not co-immunoprecipitated with MUC1 in HCT116/MUC1 cells (33). Thus, these findings suggest that phosphorylation of MUC1-CD by galectin-3 and subsequent phosphorylation of ERK1/2 and Akt occur independently of EGFR.…”
Section: Discussionmentioning
confidence: 59%
“…In addition, Tyr-46 contained in the YEKV motif is phosphorylated by several tyrosine kinases including EGFR, leading to recruitment of ␤-catenin to MUC1-CD (34). In this context, we previously demonstrated that recruitment of ␤-catenin to MUC1-CD was enhanced on treatment with Siglec-9 in HCT116/MUC1 cells and with galectin-3 in 3T3/MUC1 cells (33,53). With respect to the recruitment of ␤-catenin, it is also speculated that galectin-3- triggered signaling leads to phosphorylation of the same tyrosine residues of MUC1-CD as EGF-triggered signaling does, and after recruitment of ␤-catenin, the same pathway may occur in both signaling events.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…MUC1 engages in signal transduction through MUC1-ND-mediated ligand-binding (39,42,43) or by interacting with receptors for growth (34,40) and differentiation factors (10 -12), which contributes to the growth and survival of cancer cells. With respect to invasion and metastasis, its molecular role has not been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we reported that siglec-9, a sialic acid-binding Ig-like lectin, and galectin-3, a ␤-galactosidebinding lectin, induce the formation of the MUC1-CD/␤-catenin complex through the binding of these lectins to MUC1-ND (39,53). Since we also found that HCT116/MUC1 cells produced galectin-3 endogenously and a part of it associated on the cell surface, and that galectin-3 bound to MUC1-ND (data not shown), we speculated that the formation of the MUC1-CD/NF-B p65 complex might be enhanced by the binding of galectin-3 to MUC1-ND.…”
Section: Discussionmentioning
confidence: 99%